Electronic and optical properties of Si1-yCy alloys - Theodorou, George Os; Tsegas, George; Kelires, Pantelis C. (My University, 1999)
We investigate the electronic and optical properties of free-standing and epitaxially strained Si1-yCy alloys. We first determine the microscopic atomic structure of the alloys using the semi-grand-canonical Monte Carlo method and empirical interatomic potentials. For the calculation of the electronic and optical properties of the alloys we employ a supercell geometry and an empirical tight-binding model, which was fitted to reproduce the relevant band structures obtained from first-principles calculations. Our approach allows for a thorough investigation of C alloying and strain effects on the band gap, the band offsets, the effective masses of the upper valence and lowest conduction bands, and the optical properties. Our results are in very good agreement with experiment.
Keywords: Alloys; Monte Carlo method; Geometry